Fracture patient experience in undergoing traditional massage therapy (Topu Bara) in Maluku Province: phenomenology study - Wabula, La Rakhmat; Umamity, Syahfitrah; Fitriasari, Endah; Lombonaung, Ellen; Windari, Arindiah Puspa; Tehupelasury, Fahrunnissa (Universitas Airlangga, 2022)
Introduction: In Indonesia, especially among the Maluku people, there was a culture of seeking traditional fracture treatment, namely